Pengembangan Perangkat Pembelajaran di Sentra Persiapan Menggunakan Video Youtube di Pendidikan Anak Usia Dini - Dwi setia Mujiono; Adi Candra Kusuma (Cakrawala: Jurnal Pendidikan, 2019)
Early Childhood Education (PAUD) is one of the platforms that has been provided by the government for toddlers and young childrento be their initial foothold in the world of education. The media is used by the teacher to deliver the subject matter to students so thatlearning activities can take place effectively, efficiently, and attractively. One of the electronic media that can be used in preparationcenters is computer-based learning software. The purpose of this study is to develop a Learning Kit at the Center for Preparing to UseYoutube Videos in Early Childhood Education. This research belongs to the development research. This research method is RecearchAnd Development (R&D). This research method is used to produce certain products and assess the effectiveness of these products.Development of mathematics learning tools in the form of Syllabus, Monthly Activity Plans (RKB), Daily Activity Plans (RKH), andLearning Books preparation material for the second semester of early childhood education aged 4-6 years. The percentage of studentswho completed 19 and 90.4% presented means that students have achieved a predetermined competency that is understanding theproblems related to number recognition. In addition, students also meet the classical completeness criteria, because the percentage ofstudents who complete is 90.4%, so it can be said that overall students have achieved the specified competencies. from these resultsindicate that this learning can be said to be effective because the value of students who complete by 90.4%.